Language Functions of the Main Character in Spiderman: No Way Home Movie Script - Robert Kristian Adinata; I Gusti Ayu Vina Widiadnya Putri (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
This study focuses on the language function used by the main character in the movie